MiR-338-5p sensitizes glioblastoma cells to radiation through regulation of genes involved in DNA damage response - Besse, Andrej; Šána, Jiří; Lakomý, Radek; Křen, Leoš; Fadrus, Pavel; Smrčka, Martin; Hermanová, Markéta; Jančálek, Radim; Reguli, Štefan; Lipina, Radim; Svoboda, Marek; Šlampa, Pavel; et al. (Tumor biology, 2016)
Glioblastoma multiforme (GBM) is the most aggressive form of brain tumor. Despite radical surgery and radiotherapy supported by chemotherapy, the disease still remains incurable with an extremely low median survival rate of 12-15 months from the time of initial diagnosis. The main cause of treatment failure is considered to be the presence of cells that are resistant to the treatment. MicroRNAs (miRNAs) as regulators of gene expression are involved in the tumor pathogenesis, including GBM. MiR-338 is a brain-specific miRNA which has been described to target pathways involved in proliferation and differentiation. In our study, miR-338-3p and miR-338-5p were differentially expressed in GBM tissue in comparison to non-tumor brain tissue. Overexpression of miR-338-3p with miRNA mimic did not show any changes in proliferation rates in GBM cell lines (A172, T98G, U87MG). On the other hand, pre-miR-338-5p notably decreased proliferation and caused cell cycle arrest. Since radiation is currently the main treatment modality in GBM, we combined overexpression of pre-miR-338-5p with radiation, which led to significantly decreased cell proliferation, increased cell cycle arrest, and apoptosis in comparison to irradiation-only cells. To better elucidate the mechanism of action, we performed gene expression profiling analysis that revealed targets of miR-338-5p being Ndfip1, Rheb, and ppp2R5a. These genes have been described to be involved in DNA damage response, proliferation, and cell cycle regulation. To our knowledge, this is the first study to describe the role of miR-338-5p in GBM and its potential to improve the sensitivity of GBM to radiation.
Keywords: regulace genové exprese u nádorů; buněčné dělení; transportní proteiny; DNA Damage; Female; Protein Phosphatase 2; Radiation Tolerance; Cell Line, Tumor; ženské pohlaví; Gene Expression Regulation, Neoplastic; RNA nádorová; monomerní proteiny vázající GTP; nádory mozku; lidé; Cell Cycle Checkpoints; tolerance záření; kontrolní body buněčného cyklu; proteinfosfatasa 2; membránové proteiny; stanovení celkové genové exprese; glioblastom; Glioblastoma; Carrier Proteins; Monomeric GTP-Binding Proteins; poškození DNA; Male; Neuropeptides; mikro RNA; Brain Neoplasms; nádorové proteiny; Neoplasm Proteins; Membrane Proteins; neuropeptidy; RNA, Neoplasm; MicroRNAs; lidé středního věku; mužské pohlaví; Cell Division; Middle Aged; Gene Expression Profiling; nádorové buněčné linie; Humans